A comparative study for making compost through a handy technique - Altamirano Flores, María (2006)
The main purpose of this work is to compare two kinds of handy-technique compost within wells. One of the wells containing organic waste and dung, and the other, stubble and dung. From this experiment, comparative yields will be given, starting from compost making, its physical and chemical features, and, finally, compost quality in each of its main compounds. Our management proposal is to run a recovery program which will be useful to profit from one of the most valuable and misspent municipaluty resources: plant waste (stubble). The result could be a handy and simple compost factory to be used by municipalities.